CD40 Signaling Drives B Lymphocytes Into an Intermediate Memory‐Like State, Poised Between Naïve and Plasma Cells. Issue 10 (October 2014) - Upadhyay, Mala; Priya, G. Krishna; Ramesh, P.; Madhavi, M.B.; Rath, Satyajit; Bal, Vineeta; George, Anna; Vaidya, Tushar
Abstract Immunological memory comprising of antigen‐specific B and T cells contributes to the acquisition of long‐term resistance to pathogens. Interactions between CD40 on B cells and CD40L on T cells are responsible for several aspects of acquired immune responses including generation of memory B cells. In order to gain insights into events leading to memory B cell formation, we analyzed the genome‐wide expression profile of murine naive B cells stimulated in the presence of anti‐CD40. We have identified over 8, 000 genes whose expression is altered minimally 1.5‐fold at least at one time point over a 3‐day time course. The array analysis indicates that changes in expression level of maximum number of these genes occur within 24 h of anti‐CD40 treatment. In parallel, we have studied the events following CD40 ligation by examining the expression of known regulators of naive B cell to plasma cell transition, including Pax5 and BLIMP1. The expression profile of these regulatory genes indicates firstly, that CD40 signaling activates naïve B cells to a phenotype that is intermediate between the naive and plasma cell stages of the B cell differentiation. Secondly, the major known regulator of plasma cell differentiation, BLIMP1, gets irreversibly downregulated upon anti‐CD40 treatment. Additionally, our data reveal that CD40 signaling mediated BLIMP1 downregulation occurs by non‐Pax5/non‐Bcl6 dependent mechanisms, indicating novel mechanisms at work that add to the complexity of understanding of B cell master regulatory molecules like BLIMP1 and Pax5. J. Cell. Physiol. 229: 1387–1396, 2014. © 2014 Wiley Periodicals, Inc.